Marriage Rejection: A Feminist Study in Katie Fforde's Going Dutch - Cahyawati, Erna (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
Instead of predominantly functioning to protect women, many toxic marriages even legitimize and institutionalize patriarchal oppression. This has sparked feminist criticism, as in Katie Fforde's novel Going Dutch. Featuring a female character who rejects marriage and lives independently, this study aims to analyze two main aspects: (1) the representation of the rejection of marriage as a form of resistance to patriarchy in the novel and (2) the author's ideological position. Using a feminist approach with Stuart Hall's representation as its conceptual framework, the analysis reveals that the main character, Joana, refuses to remarry because of her traumatic experience in her previous marriage. Her husband forbids her from working or socializing outside the home. After her divorce, Joana chooses to live independently in the Netherlands, pursuing her career and hobbies while achieving economic independence and personal liberty. Through the character of Joana, Katie Fforde criticizes patriarchal norms still embedded in the institution of marriage. Going Dutch functions as a work of fiction that Ffordes advocates for women's empowerment and their right to live independently